Elegance, Myth and Empathy: Poems by Margaret Diesendorf, Alison Croggan and Fiona Perry - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
Elizabeth Perkins reviews: Margaret Diesendorf, Holding the Golden Apple, Phoenix, 1991; Alison Croggan, This is the Stone, and Fiona Perry, Pharaohs Returning, Penguin, 1991.